Police harassment and psychosocial vulnerability, distress, and depressive symptoms among black men who have sex with men in the U.S.: Longitudinal analysis of HPTN 061. (March 2021) - Remch, Molly; Duncan, Dustin T.; Geller, Amanda; Turpin, Rodman; Dyer, Typhanye; Scheidell, Joy D.; Cleland, Charles M.; Kaufman, Jay S.; Brewer, Russell; Hucks-Ortiz, Christopher; van der Mei, Willem; Mayer, Kenneth H.; et al.
Abstract: The mental health impact of exposure to police harassment is understudied, particularly among Black men who have sex with men (BMSM), a group at elevated risk of exposure to such discrimination. This study aimed to identify the associations among BMSM between recent police harassment and psychosocial vulnerability, psychological distress, and depression measured six months later. Data come from the HIV Prevention Trials Network (HPTN) 061 Study, a cohort study of BMSM recruited in 6 U.S. cities (Atlanta, GA, Boston, MA, Los Angeles, CA, New York, NY, San Francisco, CA, and Washington DC). Participants completed baseline, 6-month follow-up, and 12-month follow-up interviews. A convenience sample of 1553 BMSM was recruited between July 2009 and October 2010 of whom 1155 returned for a follow-up interview 12 months later. Accounting for previous police interaction, poverty, psychopathology, drug use, and alcohol use, we estimated associations between recent police harassment reported at the 6 month follow-up interview and 12 month outcomes including psychosocial vulnerability (elevated racial/sexual identity incongruence), psychological distress (being distressed by experiences of racism and/or homophobia), and depression. About 60% of men reported experiencing police harassment between the baseline and 6-month interview due to their race and/or sexuality. Adjusted analyses suggested police harassment was independently associated with a 10.81 (95% CI: 7.97, 13.66) point increase and 8.68 (95% CI: 6.06, 11.30) point increase in distress due to experienced racism and distress due to experienced homophobia scores, respectively. Police harassment perceived to be dually motivated predicted disproportionate levels of distress. Police harassment is prevalent and associated with negative influences on psychosocial vulnerability and psychological distress among BMSM. Reducing exposure to police harassment may improve the psychosocial health of BMSM. Highlights: We examine the impact of police harassment on Black men who have sex with men. Data from the HPTN 061 Study show that police harassment is highly prevalent. Police harassment is associated with psychosocial vulnerability. Police harassment is associated with psychological distress. Harassment motivated by racism and homophobia is associated with added distress.